Determination of disease biomarkers in Eucalyptus by comprehensive two-dimensional gas chromatography and multivariate data analysis - Hantao, Leandro Wang; Aleme, Helga Gabriela; Passador, Martha Maria [UNESP]; Furtado, Edson Luiz [UNESP]; Ribeiro, Fabiana Alves de Lima; Poppi, Ronei Jesus; Augusto, Fabio (Elsevier, 2013)
In this paper is reported the use of the chromatographic profiles of volatiles to determine disease markers in plants - in this case, leaves of Eucalyptus globulus contaminated by the necrotroph fungus Teratosphaeria nubilosa. The volatile fraction was isolated by headspace solid phase microextraction (HS-SPME) and analyzed by comprehensive two-dimensional gas chromatography-fast quadrupole mass spectrometry (GC. ×. GC-qMS). For the correlation between the metabolic profile described by the chromatograms and the presence of the infection, unfolded-partial least squares discriminant analysis (U-PLS-DA) with orthogonal signal correction (OSC) were employed. The proposed method was checked to be independent of factors such as the age of the harvested plants. The manipulation of the mathematical model obtained also resulted in graphic representations similar to real chromatograms, which allowed the tentative identification of more than 40 compounds potentially useful as disease biomarkers for this plant/pathogen pair. The proposed methodology can be considered as highly reliable, since the diagnosis is based on the whole chromatographic profile rather than in the detection of a single analyte. © 2013 Elsevier B.V..
Keywords: Comprehensive two-dimensional gas chromatography; Mass spectrometry; Metabolic profiling; Orthogonal signal correction, Unfolded partial least squares discriminant analysis; Solid phase microextraction; Analytes; Chromatographic profiles; Comprehensive two-dimensional; Disease biomarker; Disease markers; Eucalyptus globulus; Graphic representation; Headspace solid phase microextraction; Least Square; Metabolic profiles; Multivariate data analysis; Orthogonal signal correction; Partial least squares-discriminant analysis; Quadrupole mass spectrometry; Solid-phase microextraction; Volatile fractions; Chromatographic analysis; Chromatography; Mathematical models; Metabolism; Multivariant analysis; Plants (botany); Smoke detectors; Diagnosis; 2 hexanal; 2,2 dimethyl valeraldehyde; 2,4 hexadien 1 ol; alpha bulnesene; alpha cadinene; aromadendrene; beta eudesmol; biological marker; camphene hydrate; careen; carveol; carvone; cineole; citral; copaene; geraniol; geranyl acetate; humulene; ledol; myrcene; nerolidol; perillen; pinene; solusterol; terpinene; terpineol; trans 3 caren 2 ol; unclassified drug; valencene; viridiflorol; controlled study; disease marker; fungal plant disease; fungus; gas chromatography; mass fragmentography; multivariate analysis; nonhuman; partial least squares regression; plant leaf; predictive value; priority journal; reliability; solid phase microextraction; Teratosphaeria nubilosa; validity; Eucalyptus; Fungi; Teratosphaeria